A Fourier perspective of freeway traffic - Lino Figueiredo (2004)
This paper presents the Simulator of Intelligent Transportation Systems (SITS) and a dynamical analysis of several traffic phenomena. The SITS is based on a microscopic simulation approach to reproduce real traffic and considers different types of vehicles, drivers and roads. In order to process the resulting information, it is also introduced a new modelling scheme based on the embedding of statistics and Fourier transform. The results point out that it is possible to study traffic systems, taking advantage on the knowledge gathered with systems theory.